Residential care home management in London - Mogaji, Emmanuel (London : SAGE Publications: SAGE Business Cases Originals, 2019)
Arnold is an Area Manager employed by MetCare, a Residential Care Services provider in London. One of their projects--Osborne House--is up for tender. Arnold is tasked with assessing the complexities of managing a residential care home in London and offering a solution to improve efficiencies, reduce costs, sustain profitability and maintain service quality. He has conducted meetings with the Registered Care Home Manager and the Support Workers to identify their concerns about providing adequate care to residents.This business case aims to examine the challenges of managing residential care homes, the implications of limited government funds and the changing demands of the customers on staff morale. It further explores the managerial implications of those challenges and identifies how the management can support the staff to deliver adequate service in the face of the challenges in the adult social care service industry in the UK.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Metcare -- Case studies; Nursing homes -- Great Britain -- Management -- Case studies; Life care communities -- Great Britain -- Management -- Case studies